Comparative seasonality of phytoplankton community in two contrasting temperate estuaries on the western coast of Korea - Kim, Dongyoung; Sung, Je Won; Kim, Tae-Hoon; Cho, Hyung-Mi; Kim, Jeonghyun; Park, Hyun Je (Frontiers in Marine Science, 2023)
In estuaries, freshwater discharge functions as a regulator of physicochemical and biological properties. We assessed the seasonal variability of the phytoplankton community in response to hydrological features and nutrient dynamics in two contrasting estuaries in the presence and absence of a dam on the western coast of Korea. Diversity and evenness were also evaluated through chemotaxonomic analysis. Seasonal and inter-estuarine comparisons revealed the overall predominance of diatoms in all seasons and the differentiated composition of small phytoplankton populations in each estuary, which was mainly characterized by significant contribution of cryptophytes in the continuously flushed estuary in contrast to the seasonal occurrence of pelagophytes and cyanobacteria in the intermittently perturbed estuary. Our one-way analysis of similarity and similarity percentage analysis showed obvious inter-estuarine discrepancy of the phytoplankton community in winter in relation to the high dissolved inorganic nitrogen concentration in the natural estuary, implying that the impact of freshwater inflow on the phenological response of phytoplankton can be maximized during active seawater intrusion in dry seasons in the prevalence of freshwater and seawater in the estuary. The contribution swing of diatoms and cryptophytes during the study period reflects the seasonal variability in nutrient dynamics, including absolute concentrations and stoichiometric ratios, which is especially associated with P-limitation on the western coast of Korea. The occurrence of cyanobacteria with a summer peak of phytoplankton biomass in the dammed estuary during the study period indicates the role of an estuarine dam as a conduit transporting phytoplankton and dissolved inorganic nutrients. These findings further suggest that the phytoplankton community structure, differentiated by the presence and absence of dams, influences bottom-up regulation and thus the food web structure in estuaries.